THE RELATIONSHIP BETWEEN SOCIAL MEDIA WORD-OF-MOUTH, CONSUMER-BASED BRAND EQUITY AND CONSUMER RESPONSE AMONG AUTOMOTIVE CONSUMERS IN MALAYSIA - Ridwan Adetunji Raji; Sabrina Mohd Rashid; Sobhi Mohd Ishak (Lingkar Studi Komunikasi (LISKI), 2017)
The literature on Consumer-Based Brand Equity (CBBE) continues to grow enormously. Previous studies on CBBE have maintained that marketing communications play a significant role in developing CBBE. Furthermore, researchers have argued that social media has become a renowned and strategic platform for disseminating brand-related communication. Hence, the advent of brand-related communication on social media is as well increasing the freedom and involvement of consumers in the co-creation of brand-related contents, thus giving rise to Social Media Word-of-Mouth. However, researchers have paid little attention to determining the role of Social Media Word-of-Mouth in developing CBBE and evoking favourable consumer behaviour. Therefore, this study sets out to examine the relationships between Social Media Word-of-Mouth, CBBE and Consumer Response. For this purpose, 290 consumers of two automotive brands were surveyed using the survey questionnaire. The data collected was analysed using both SPSS version 23 and AMOS version 23. The results revealed that Social Media Word-of-Mouth is important for enhancing CBBE and stimulating Consumer Response. Consequently, brand managers and marketers of automotive brands in Malaysia were charged to increase their engagements and investments in social media communications and encourage favourable word-of-mouths from their consumers on social media in order to improve the acceptance of their brands and increased positive consumer behaviour. This study concludes that consumer reviews, comments and posts on social media have significant implications on brands and consumer behaviour.